Surveying physical activity and nutritional status of pediatric leukemia patients - Alhajri, Ahlam Saleh (Frontiers in Nutrition, 2025)
BackgroundPediatric leukemia treatment often leads to challenges in maintaining adequate physical activity and nutritional status, both of which are crucial for overall health and recovery. Despite their importance, few studies have explored the interplay between physical activity, nutrition, and treatment stages in children undergoing leukemia treatment.AimThis study aimed to evaluate the physical activity levels and nutritional status of pediatric leukemia patients, examining how these factors vary by gender, age, leukemia type, and treatment stage.MethodsA cross-sectional survey was conducted among 337 pediatric leukemia patients aged 6 to 12 years in Saudi Arabia. Data on physical activity and dietary habits were collected using an online questionnaire. Descriptive statistics, T-tests, and ANOVA were used to analyze the data.ResultsThe study found that 60% of participants failed to meet recommended physical activity levels. Males had significantly better nutrient-rich diets compared to females (Mean = 4.22 vs. 2.86, p < 0.0001). Children in the remission phase reported the lowest engagement in physical activity (Mean = 2.53, p < 0.0001), while those in the maintenance phase exhibited the highest energy levels (Mean = 4.45, p < 0.0001). Age differences were significant in motivation to participate in physical activities, with children aged 8–9 years reporting higher motivation (Mean = 2.97, p = 0.0249).ConclusionThe study highlights significant differences in physical activity and nutritional status based on gender, age, leukemia type, and treatment stage. Integrating personalized physical activity and nutritional interventions into pediatric leukemia care is essential for improving health outcomes and quality of life during treatment.